Dienvidlatgales izlokšņu un lietuviešu valodas paralēles vārddarināšanā - Reķēna, Antoņina (Baltistica, 1996)
PARALLELS IN WORD-BUILDING OF SOUTHERN LATGALE SUBDIALECTS AND LITHUANIAN 1. In Southern Latgale subdialects there are dialectisms of word-building which have a counterpart in the Lithuanian or Prussian. In standard Latvian there may be similar roots or affixes, but there are no analogues in word-building, e.g., vìrsûne, Lith. viršū́nė; vìlcìene, Lith. vilkíenė; zûosìns, Lith, žą̃sinas, màlinis, Lith. mólinis; baĩme, Lith, báimė, kàlvis, Lith. kálvis, palazde, Lith. palazdė̃; etc. 2. The comparative analysis of the facts of Southern Latgale subdialects obtained point to the ancient connections between the Eastern Baltic tribes – the Latgalians, the Selonians and the Lithuanians and to the more ancient and newer dwelling places of Lithuanians in Southern Latgale and Sēlija and to the historical fate shared by the above-mentioned tribes after 1561. 3. In Southern Latgale the characteristics and the influence of the Baltic Finns are the weakest compared to the other ethnographical regions of Latvia, including Northern Latgale. Eastern Latgale and Central Latgale – the Baltic adjectives with -inis, -ine are preserved, whereas words of Finnish origin, hydronyms, etc are encountered more rarely. 4. The dialect vocabulary of the Latgale subdialects points to the stability of the inherited facts of language which in a number of cases have not been influenced by the sociolinguistic situation.